RECENT ADVANCES IN DENTAL SCIENCE - A BRIEF REVIEW - S., Ragul Prasath; Priya. A, Jothi (International Journal of Psychosocial Rehabilitation, 2020)
The most important goal in dentistry is to provide the best dental care to the patients. However, this may be attained with the help of a skilled dental professional and it's team. As the years pass by, several advances in science, especially in medicine, are leading humanity towards a new era of dentistry. Professionals and clinical experts with decades of experience or a dental student can look back at the advancements made in dentistry and can say clearly that the dental profession has experienced an exciting amount of technological growth. But in comparison to medicine, biomedical engineering, automobiles and aeronautics, drugs, and others, dentistry appears to be more than a decade behind in adopting or integrating new technologies on a widespread basis. Dentistry has witnessed tremendous advances in all its branches over the past three decades.Starting from the simple intra-oral periapical X-rays to advanced imaging techniques like CT scans (computed tomography), cone beam computed tomography, MRI scans (magnetic resonance imaging), and ultrasound techniques have also found place in modern dentistry. This significant shift from analogue to digital radiography has not only made the procedures simpler and faster but also made image storage, manipulation like image, brightness/contrast, cropping, etc., and retrieval easier. This review article focuses on the various future perspectives of dentistry and their clinical applications.With the development of new technologies in three dimensions and computer-aided design/computer-aided manufacturing (CAD/CAM), customized implants can be used as an alternative to conventional implant designs